2019
DOI: 10.1080/13621718.2019.1695347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction stir and activated-GTA welding processes on the 9Cr–1Mo steel to 316LN stainless steel dissimilar weld joints

Abstract: The consequence of friction stir welding (FSW) and activated-gas tungsten arc welding (A-GTAW) processes on the evolution of microstructure and mechanical properties of 9Cr-1Mo (P9) steel to 316LN stainless steel dissimilar weld joint is investigated. The FSW specimen shows considerably higher tensile strength ( ∼ 652 MPa) compared to A-GTAW specimen ( ∼ 595 MPa) as well as its base metal of P9 ( ∼ 642 MPa) and 316LN ( ∼ 608 MPa) owing to the formation of tempered martensite and refined austenite in P9 and 316… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Narrow HAZ was formed closer to the SZ and LN-type 316 SS owing to the low thermal conductive property. In an EBSD research, 26 it is revealed that the average distribution density of low angle grain boundary (LAGB) and high angle grain boundary (HAGB) of 316LN BM was ∼9.7% and ∼90.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Narrow HAZ was formed closer to the SZ and LN-type 316 SS owing to the low thermal conductive property. In an EBSD research, 26 it is revealed that the average distribution density of low angle grain boundary (LAGB) and high angle grain boundary (HAGB) of 316LN BM was ∼9.7% and ∼90.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Specimens welded by the FSW process have HAZs smaller than the specimens joined by fusion welding. For instance, tungsten arc welding was reported to produce HAZs with great widths due to the relatively high heat input [71,72], which may result in the failure of joints created by fusion welding [73]. Comparatively, FSW generates lower heat in the HAZ.…”
Section: Friction Stir Welding (Fsw) Of Steelsmentioning
confidence: 99%
“…This may negatively affect the mechanical properties of the welded joints due to the inhomogeneous distribution of the chemical composition [77,78]. On the other hand, because of the tempered martensite formation and the refined austenite in the SZ, FSW specimens showed higher tensile strength than the specimens joined by activated-gas tungsten arc welding of 9Cr-1Mo and 316LN stainless steel [72].…”
Section: Friction Stir Welding (Fsw) Of Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 GTA welding being the most suitable and trusted on-site welding process in the fabrication of stainless steel structures. 6 Nevertheless, an important inadequacy of the GTAW process is that the welding is carried out in a single pass and limited to a limited plate thickness. 7 In order to overcome this disadvantage, plates with a thickness higher than 6 mm are usually joined with the use of activating flux of oxides or perform multi-pass welding to attain full depth of penetration.…”
Section: Introductionmentioning
confidence: 99%